Pemanfaatan Tepung Mocaf sebagai Bahan Subtitusi terhadap Produk Nastar Gluten Free - Qhonif, Laila; Wardana, Miko Andi (Penerbit Goodwood, 2024)
Purpose: The purpose of the research on the Utlization of Mocaf Flour (Modfied Casava Flour) as a Substitution Mterial fr Nastar Gluten Free Products is to innovate the manufacture of pineapple with the substitution of mocaf flour as an effort to provide the benefits of consuming cookies in a healthier way where nastar cookies with the use of mocaf flour can be enjoyed by all people from children to the elderly.Research methodology: This study uses qantitative methds with a type of exprimental research in the form of results obtained from panelists on the quality test of nastar from mocaf flour both in trms of tastess, colr, txture, and arma with organoleptic tests.Results: The results of this study are in the form of a manufacturing process that has no difference, the quality of gluten free nastar made from mocaf flour is very good in terms of taste, very fragrant aroma, very soft texture and has a very yellow color. From the results of the endurance test of gluten free nastar made from mocaf flour, it can last for 7 days. In this study, researchers gave questionnaires to 50 panelists with 35 untrained panelists and 15 panelists from the field of gastronomy. From the results of the cost analysis in making gluten free nastar made from mocaf flour costs Rp 40,375. Conclutions: Nastar made from mocaf flour has excellent sensory qualities in taste, color, texture, and aroma, so it can be an alternative to wheat flour. Although the production cost is relatively higher due to the fermentation process, the ingredients used are still easy to obtain. This product has the potential to be developed as a local food innovation that is friendly to people with gluten intolerance.Limitations: This study has limitations in terms of production scale and cost efficiency, where the production cost of nastar made from mocaf flour is still higher compared to nastar made from wheat flour. In addition, this study has not tested the product's shelf life and consumer response on a wider market scale.Contributions: This research contributes to the innovation of mocaf flour-based food products as an alternative for people with gluten intolerance. In addition, this research also supports the diversification of products based on local ingredients that can increase added value for the Indonesian food industry.Keywords: Cookies, Mocaf, Nastar, Organoleptic Test How to cite: Qhonif, L. Wardana, M, A. (2024). Pemanfaatan Tepung Mocaf sebagai Bahan Subtitusi terhadap Produk Nastar Gluten Free. Jurnal studi perhotelan dan pariwisata, 3(1), 41-47.